PELATIHAN PENGGUNAAN APLIKASI ZOOM DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR INPRES MAULAFA KOTA KUPANG - Juliana M. H. Nenohai; Patrisius A. Udil; Irna Karlina Sensiana Blegur (Bakti Cendana, 2022)
The aim of this Community Service (PkM) activity is to facilitate low-grade teachers of SD Inpres Maulafa Kupang City, East Nusa Tenggara, using the zoom application as an online conference media in mathematics learning which is carried out online during the covid 19 pandemic. The PkM team from the Mathematics Education Study Program, Nusa Cendana University, collaborating with the head of SD Inpres Maulafa, Kupang City. There were 35 low-grade teachers and staff of SD Inpres Maulafa, Kupang City who actively participated in the workshop. The PkM activity started by presentation of classically relevant material. There are two topics 1). The importance of technology integration in mathematics learning and 2). a brief explanation of the zoom application, the supporting features and procedures for managing the zoom application for online learning. The activity continued with discussion then direct practice by teachers and staff related to the theory that had been explained. The results showed that the participants were very enthusiastic about the material being studied and there needed to be further activities to facilitate teachers using other simple video conferencing applications in learning. The activity ended with the awarding of prizes where participants received a certificate of participation in the activity.